Penerapan value stream mapping untuk peningkatan produktivitas produksi okra beku di PT. MDT - Ida Bagus Suryaningrat; Bambang Herry Purnomo; Fatimah Fatimah (AGROINTEK, 2022)
The frozen food industry continues to grow and needs attention to maintain productivity and quality of the product. Value Stream Mapping (VSM) is an appropriate method to evaluate and increase productivity in lean manufacturing. PT. MDT is a company engaged in the business focusing on processing okra vegetables. This company has never assessed the okra production process. Minimizing the lead time of the process and cycling time of daily activities are problems related to productivity in this company. This study aims to reduce processing time to develop recommendations to improve the okra production process. VSM and comparative analysis of the current and future state maps were implemented in this study to establish proposed recommendations. Process Activity Mapping (PAM) resulted from the current state; total value-added was 186.31 minutes, necessary non-value-added was 26.99 minutes, and non-value added was 543.41 minutes. The highest non-value added value was found in the queue of raw materials at the material staging area (MSA) and weighing. Proposed recommendations for improvement solutions at MSA were to set up the engine warm earlier and reduce set-up time, good production planning, and implement the kanban system. At the same time, the queue of raw materials at weighing was to supervise and add operators. Solutions were implemented into a future state map. The total lead time was 371.35 minutes, and the value-added was 213.30 minutes. The comparison of the current state map and future state map showed decreasing of 48.37% in the MSA lead time, 66.69% in weighing, and 31.66% in the total lead time. Based on the lead time of the current condition map, one shift of production could produce 112 boxes. Meanwhile, with a lead time map of future conditions, this could produce 202 boxes